Understanding maternal Ethnomedical Folklore in Central Uganda: a cross-sectional study of herbal remedies for managing Postpartum hemorrhage, inducing uterine contractions and abortion in Najjembe sub-county, Buikwe district - Alice Nabatanzi; Abdul Walusansa; Joanita Nangobi; Doreen Apio Natasha (BMC, 2024)
Abstract Pregnant women in rural Uganda largely rely on medicinal plants for inducing labor, treating postpartum hemorrhage (PPH), and inducing abortion. 90% of the women in both rural and urban Uganda use plants to manage pregnancy symptoms like constipation, heartburn, morning sickness, body aches, nausea, and vomiting. After delivery women continue using plants to manage postpartum complications and for infant care especially herbal baths. This study documented how ethnomedical folklore has been used to aid childbirth, manage postpartum hemorrhage, and induce abortion. Methods A cross-sectional ethnobotanical survey was conducted from May - December 2023 in Najjemebe sub-county, Buikwe district. 206 respondents from 12 villages were selected using snowball sampling. Key informants included Traditional Birth Attendants (TBAs) and herbalists. Data was collected using semi-structured questionnaires and focus group discussions. Voucher specimens of the plants were identified and authenticated at Makerere University Herbarium. Data were analyzed using descriptive statistics, Informant Consensus factor (ICF), Use Reports (URs), paired comparisons, and GraphPad Prism® version 9.0.0 software. Results All respondents (N = 206, 100%), used plants to induce labour, treat PPH, and induce abortion. One hundred four plant species were documented: most cited or preferred were: Hoslundia opposita (N = 109, 53%), Phytolacca dodecandra (N = 72, 35%), and Commelina erecta (N = 47, 23%). The plants belonged to 49 families, Lamiaceae (16.3%) and Fabaceae (14.3%) having the majority of the species. Herbs were 42 (40%) and trees 23 (22%). Oral administration 95(72%) was the commonest, then topical 19 (14.4%) and vaginal 14(10.6%). Conclusion Health surveys revealed that about 27% of deliveries in Uganda take place outside a health facility. Due to the oxytocic effects of plant species reported in this study, they play a triple role of being uterotonics, abortifacients, and treating postpartum haemmorhage. The dilemma lies in the unknown dosages and toxicity levels that could endanger both the mother's and the unborn child's lives. Due to Uganda's high rates of population growth, overall fertility, maternal mortality, and morbidity, policies, and programmes on gendered health provision need to be reevaluated. Integrating herbal medicine into health care systems appears to be a feasible solution.